Digital Business Model Innovation And Smes Competitiveness: The Contingent Role Of Organizational Culture - Teoh, Ming Fang (2022)
Small and medium-sized enterprises (SMEs) play a predominant role in fostering the digital economic performance of Malaysia. Achieving this requires innovating digital business models to improve the flexibility and speed of SMEs responding to market changes in a volatile digital landscape. Anchored on upper echelon theory, dynamic capabilities theory, and institutional theory, this study endeavours to investigate the relationship between entrepreneurial leadership, digital capability, and government support with digital business model innovation (DBMI) adoption (i.e., value creation innovation, value proposition innovation, value delivery innovation, and value capture innovation). This research examines the outcome of DBMI on SMEs’ competitiveness and the moderating effect of organizational culture in the relationship between DBMI and SMEs’ competitiveness in the context of SMEs, Malaysia.